Effects of high-temperature pre-drying on the quality of air-dried shiitake mushrooms (Lentinula edodes). (1st July 2019) - Xu, Lei; Fang, Xiangjun; Wu, Weijie; Chen, Hangjun; Mu, Honglei; Gao, Haiyan
Highlights: High-Temperature Pre-drying increased the rehydration ratio/hardness of dried products. High-Temperature Pre-drying decreased the shrinkage/browning degree and formaldehyde content. High-Temperature Pre-drying enriched the aroma components of dry Lentinula edodes, which makes it better quality. Abstract: We investigated the relationship between the pre-drying temperature and overall quality of dried shiitake mushrooms (Lentinula edodes). Results showed that high-temperature pre-drying significantly increased the rehydration ratio and hardness of dried shiitake mushrooms, but decreased the degree of shrinkage, degree of browning, and formaldehyde content. The levels of enzyme activity were high throughout the pre-drying process and benefitted the formation of flavoured substances. Furthermore, high-temperatures pre-drying also resulted in a higher content of sulfur compounds. These results indicated that the pre-drying processing had significant impacts on the overall quality of dried shiitake mushrooms. This may pave the way for increasing the economic value of dried shiitake mushrooms.